Hypermethylation of the Gene Coding for PGC-1α in Peripheral Blood Leukocytes of Patients With Parkinson’s Disease - Yang, Xiaodong; Xu, Shaoqing; Qian, Yiwei; He, Xiaoqin; Chen, Shengdi; Xiao, Qin (Frontiers in Neuroscience, 2020)
Decreased expression of peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) is implicated in the pathophysiology of Parkinson’s disease (PD). However, our understanding of the mechanism of regulating PGC-1α expression is still limited. We sought to determine whether epigenetic modification of PPARGC1A (the gene encoding PGC-1α) could account for its diminished expression. We performed a study of PPARGC1A risk-SNP genotypes, methylation level, and expression in blood from 171 subjects. The mean DNA methylation level of PPARGC1A intron 1 in patients with PD was higher than that in controls (7.18 ± 1.74 vs. 6.36 ± 1.28, P = 0.007). A detailed comparison of DNA methylation level at each CpG site showed that CpG_1, CpG_13.14, CpG_17.18 and CpG_20 were significantly hypermethylated in patients with PD. There was a significant negative correlation between PPARGC1A methylation and expression level (R = -0.404, P < 0.001). We found no correlations between the PPARGC1A methylation level and clinical features, while the CpG_13.14 site methylation level was positively correlated with H-Y stage (R = 0.246, P = 0.020) and was increased in people carrying the rs2970848 AA genotype compared with carriers of the AG/GG genotype (7.27 ± 1.86 vs. 6.65 ± 1.92, P = 0.032). Our results support a link between PPARGC1A methylation, gene expression and variability, which indicated a novel epigenetic regulatory mechanism controlling PPARGC1A expression influences PD pathogenesis.